LncRNA H19 Overexpression Activates Wnt Signaling to Maintain the Hair Follicle Regeneration Potential of Dermal Papilla Cells - Zhu, Ningxia; Lin, En; Zhang, Huan; Liu, Yang; Cao, Guiyuan; Fu, Congcong; Chen, Le; Zeng, Yang; Cai, Bozhi; Yuan, Yanping; Xia, Bin; Huang, Keng; et al. (Frontiers in Genetics, 2020)
Androgenetic alopecia is a common hair loss disorder resulting in seriously abnormal social interaction and psychological disorders. Transplantation with autologous dermal papilla cells represents a prospective therapy. However, the ability of dermal papilla cells to induce hair follicle development is lost upon cell culturing. Long noncoding RNAs (lncRNAs) are an important class of genes involved in various biological functions, are aberrantly expressed in disease and may play roles in the regulation of Wnt signaling, a critical pathway in maintaining the hair follicle-inducing capability of dermal papilla cells. Examination of dermal papilla cells by lncRNA microarray revealed that H19 was highly expressed in early-passage dermal papilla cells compared with late-passage dermal papilla cells. In this study, we constructed H19-overexpressing dermal papilla cells to examine the role of H19 on hair follicle inductivity. Dermal papilla cells infected with lentivirus encoding H19 maintained their cell shape, and continued to display both multiple-layer aggregation and hair follicle-inducing ability upon prolonged culture. H19 exerted these effects through inducing miR-29a to activate Wnt signaling by directly downregulating the expression of Wnt suppressors, including DKK1, Kremen2 and sFRP2, thereby forming a novel regulatory feedback loop between H19 and miR-29a to maintain hair follicle- inducing potential. These results suggest that lncRNA H19 maintains the hair follicle-inducing ability of dermal papilla cells through activation of the Wnt pathway and could be a target for treatment of androgenetic alopecia.